Rethinking the place of crime in police patrol: a re-reading of classic police ethnographies - Ranasinghe, Prashan (The British journal of criminology, 2017)
Both in the policing literature and criminology more broadly, it is a taken-for-granted fact—an entrenched ‘truism’—that patrol policing has little to do with crime. This ‘truth’ is a product of fieldwork on the public police begun in the early-1950s. These works, thus, are of immense importance to criminology. In this paper, I undertake a re-reading of several classic police ethnographies and argue that there is a disjuncture between what is claimed and revealed. These texts show that the patrol police appear to deal with a significant amount of what I call crime work, the minimization and marginalization of which I seek to make sense of.